A world of flavours Thailand : authentic regional recipes - Watson, Christine (United Kingdom : Apple Press, 2009)
A guide to Thai cooking. It features over 100 recipes ranging from quick, convenient noodle dishes and stir-fried greens to hot and sour soups and creamy Thai curries.
Introduction -- Classic Dishes -- Northern Thailand -- Northeastern Thailand -- Central Thailand -- South Thailand -- Index.
Includes index.
Keywords: COOKING, THAI